Worthwhile aims? A qualitative study into experiences of funding within elite sport - Foster, E. (2019)
Since the awarding of the London 2012 Olympic Games in 2005, elite sport has enjoyed an increasing amount of public support and interest, yet the origins of this go far further back than most appreciate. As the level of British sporting achievement increases, so does the cost; with the Tokyo 2020 Olympic cycle costing £245million (UK Sport, 2016). Numerous studies have examined elite sport and the financial cost as a burden on an individual nation, but few studies directly address the financial impact elite sport has on the individual athlete. Using both qualitative interviews and findings from my own personal reflection, this study seeks to explore how individual athletes within a single Olympic sport experience funding: the financial and emotional pressures, along with explanations of why and how athletes manage this situation, utilising the theories of Pierre Bourdieu. Key research questions address UK Sport`s current remit and sustainability, and the burden placed on individual athletes. The findings from both elements of the research corresponded with each other: athletes felt large amounts of pressure, relating to both present and future sporting performance due to funding issues, and explanations of why athletes accepted this level of pressure are explained using the theory of capital.